2010
DOI: 10.1002/pssc.200982609
|View full text |Cite
|
Sign up to set email alerts
|

Built‐in fields in non‐polar InxGa1–xN quantum dots

Abstract: We present a detailed analysis of the internal built‐in potential in polar and non‐polar Inx Ga1–x N quantum dots (QDs). The applied model is based on a surface integral method to calculate the three‐dimensional electrostatic built‐in potential in semiconductor QDs of arbitrary shape. This technique allows for a detailed and systematic analysis of the different contributions to the total built‐in field. Here, we also investigate the impact of the QD geometry on the built‐in potential in structures grown along … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…3 The electrostatic built-in field and its impact on the electronic and optical properties have been studied theoretically. 6,8,9 The properties of a-plane GaN/AlN QDs have been discussed in Ref. 6.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…3 The electrostatic built-in field and its impact on the electronic and optical properties have been studied theoretically. 6,8,9 The properties of a-plane GaN/AlN QDs have been discussed in Ref. 6.…”
mentioning
confidence: 99%
“…Their geometrical features deviate significantly from the previously assumed truncated pyramidal or lens-shaped QD shapes. 6,8,9 To date no detailed analysis of the built-in field, the electronic, and the optical properties has been performed for arrowhead-shaped structures. Therefore, the aim of this work is to present a detailed analysis of realistic arrowhead- shaped a-plane GaN/AlN QDs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work has demonstrated active III‐nitride semipolar light‐emitting diodes and lasers in the green and blue region of the spectrum . Analysis of the internal built‐in polarization potential of nonpolar InGaN/GaN QDs showed strong reduction with increasing Ga content (). Comparison between polar and semipolar InGaN/GaN QDs showed blue‐shifted emission of the PL for the semipolar nanostructures compared to the polar ones, but this was attributed to lower indium incorporation in the semipolar case ().…”
Section: Introductionmentioning
confidence: 99%
“…7 Theoretical work has shown that the QCSE can be nearly eliminated in nonpolar InGaN QD systems with lower In concentration. 8 Furthermore, nonpolar and semipolar nitride systems can exhibit other interesting properties such as the larger exciton binding energy compared with the polar systems. 9,10 Therefore, it is desirable to grow InGaN QDs on the nonpolar and semipolar surfaces.…”
mentioning
confidence: 99%